Innovative Construction Technique Using Ferrocrete (International Journal of Scientific Research and Management (IJSRM), 2016)
In recent years, speedy construction is necessary for overall development to satisfy the needs of current population. There is huge mismatch between the infrastructural needs and its development. This study aims to increase the pace of construction using precast ferrocrete mould which would eradicate the use of formwork completely. Significant amount of work has been carried out on confinement of column with ferrocrete laminates for strengthening and jacketing purposes. Use of ferrocrete mould as an external confinement to concrete specimen has been thoroughly studied and investigated in this experimental study. The experimental investigation included casting of six M20 blocks in two batches each having different specifications. All the specimens were tested for direct un-axial compression. The change in stress carrying capacity of confined specimens was compared with that of unconfined specimens having similar size and dimensions. After comparison, the increase in load carrying capacity observed in ferrocrete confined specimens was 71.18%, as compared to the strength of unconfined specimens.